DINAMIKA POPULISME ISLAM PASCA REFORMASI DI INDONESIA - Puteri Atikah; Rholand Muary; Ramdeswati Pohan (FISIP Universitas Malikussaleh, 2025)
This paper analyzes the dynamics of Islamic populism in post-Reform Indonesia using a political economy approach. Islamic populism is understood as a response to political marginalization and economic inequality experienced by Muslims from the colonial era to the present. This phenomenon not only manifests in electoral contests through the mobilization of religious identity but also in the form of hijrah movements and Islamic popular culture targeting the urban middle class. Drawing on literature concerning the historical marginalization of Islamic politics, electoral dynamics, and religious expression in cultural and digital spaces, this study shows that Islamic populism is often exploited by oligarchic elites as a symbolic political mobilization strategy. Islamic identity is commodified and channeled through market logic, rendering it an instrument that reinforces the status quo rather than a transformative force. Therefore, Islamic populism represents structural grievances of the Muslim community that are utilized by dominant powers, rather than a movement capable of substantively addressing social inequality.